Kekuatan dan Kebutuhan Perancah Ringlock Scaffolding System Pada Proyek Pembangunan Gedung Fasilitas Pengembangan Produk Skala Pilot (Gedung No.34) PT. Biofarma - Wahyu Surya Daru Saputra; Abdul Rochman (Jurnal Talenta Sipil, 2023)
The causeway for project workers uses a scaffolding device for road safety for project workers which is focused on holding the load according to the dimensions of the tool. In the Pilot Scale Product Development Facility Building Project (Building No.34) PT. Biofarma used the Ringlock scaffolding System type of scaffolding. Ringlock Scaffolding System. Direct observation in the field. The maximum load that can be supported by the Vertical Standard is 2,000 kg, the reduction value is 0.5 due to unpredictable field conditions. 1,000 kg is the most weight for a scaffolding pole. In the ringlock scaffolding scaffolding for the construction of building No. 34 PT. Biofarma 1,000 kg > 984.7746 kg which means sturdy and strong.